2005
DOI: 10.1128/aac.49.6.2421-2428.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Imipenem during Continuous Renal Replacement Therapy in Critically Ill Patients

Abstract: The pharmacokinetics of imipenem were studied in adult intensive care unit (ICU) patients during continuous venovenous hemofiltration (CVVH; n ‫؍‬ 6 patients) or hemodiafiltration (CVVHDF; n ‫؍‬ 6 patients). Patients (mean ؎ standard deviation age, 50.9 ؎ 15.9 years; weight, 98.5 ؎ 15.9 kg) received imipenem at 0.5 g every 8 to 12 h (total daily doses of 1 to 1.5 g/day) by intravenous infusion over 30 min. Pre-and postmembrane blood (plasma) and corresponding ultrafiltrate or dialysate samples were collected 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 43 publications
5
47
3
Order By: Relevance
“…The impacts of two CRRT procedures, CVVH and CVVHDF, on the disposition of doripenem and doripenem-M-1 were also rigorously assessed. The mean Sc and Sa for doripenem were comparable with those from previous reports of imipenem and meropenem, in which the same hemofilter was used (10,13,21). The CL CRRT of doripenem accounted for 25 to 32% of the observed CL, and the mean values ranged from 82 to 92% of simultaneous CL urea values, clearly indicating that either mode of CRRT has a marked effect on the disposition of doripenem, which needs to be accounted for with an increase in the daily doripenem dosage.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The impacts of two CRRT procedures, CVVH and CVVHDF, on the disposition of doripenem and doripenem-M-1 were also rigorously assessed. The mean Sc and Sa for doripenem were comparable with those from previous reports of imipenem and meropenem, in which the same hemofilter was used (10,13,21). The CL CRRT of doripenem accounted for 25 to 32% of the observed CL, and the mean values ranged from 82 to 92% of simultaneous CL urea values, clearly indicating that either mode of CRRT has a marked effect on the disposition of doripenem, which needs to be accounted for with an increase in the daily doripenem dosage.…”
Section: Discussionsupporting
confidence: 75%
“…The clearances of imipenem by CVVH ranged from 6.5 to 13.3 ml/min in the 1990s and have increased to 22.9 to 36.0 ml/min during the last decade (9,10,21). This increase is in part due to the utilization of larger-surface-area hemofilters and higher ultrafiltration rates.…”
Section: Discussionmentioning
confidence: 96%
“…The sieving coefficients observed in our study differed dramatically from those reported by Cirillo et al A possible explanation for the difference between prefilter/ postfilter clearance and sieving coefficient-dependent clearance could be adsorption of doripenem to the filter membrane. The prefilter/postfilter clearance values found in our trial are within the range of values reported previously for imipenem (36 Ϯ 13 ml/min with CVVH and 57 Ϯ 32 ml/min with CVVHDF) and meropenem (49 Ϯ 8.3 ml/min with CVVH), although the membrane sizes in our trial were considerably larger than those in the previous studies (12,13). Our data show an uncharacteristically low clearance for CVVHDF patients, which may be attributed to the larger membrane size and higher membrane k UF employed for the CVVHF and CVVHD groups.…”
Section: Resultscontrasting
confidence: 48%
“…Given that sampling was not performed during the distribution phase, standard first-order equations were used to calculate the pharmacokinetic (PK) parameters of interest. The percent of time that the free piperacillin plasma level was above the minimum inhibitory concentration (MIC) during the dosing interval (%T.MIC) was calculated for MIC of 16 and 64 mcg/ml using previously reported methods (8,9). A pharmacodynamic (PD) target for piperacillin of .50%T.MIC64 mcg/ml was selected as the parameter of interest based on prior publications and proportion with target achievement calculated (10).…”
Section: Pharmacokinetic and Pharmacodynamic Calculationsmentioning
confidence: 99%